Setting the stage for special needs theatre - R, Chandran (Institutional Knowledge at Singapore Management University, 2019)
When I was a child, my special ability was in sports. I was good at football, badminton and sprinting, and even had aspirations of being a professional sportsman when I grew up. However, in terms of pursuing a sustainable sporting career, I was ahead of my time by a few generations.